Reliability of Divided Small Electric Energy System - Deveikis, T.; Miliune, R.; Nevardauskas, E. V. (Elektronika ir Elektrotechnika, 2013)
Reliability is one of the most important factors of electrical energy system. This paper presents analysis of reliability of electrical energy system and divided small electrical energy system. To meet stated requirements of reliability is needed to increase energy supply reliability by increasing equipment reliability, distributing energy generation and creating smaller electric energy systems during fault period. The small electrical energy system creation impact to energy supply reliability has been investigated for defined divided electrical energy system during occurrence of a fault. The main reliability parameters of electrical equipment have been identified and calculated. Reliability of different small electrical energy system regimes has calculated and compared. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.2727